Considering poststructuralist discursive community psychology. Issue 4 (4th March 2022) - Malherbe, Nick; Cornell, Josephine
Abstract: Although critical community psychology (CCP) has embraced several discursive paradigms (e.g., critical discourse analysis, discursive psychology, and Foucauldian discourse analysis), there remains little CCP work that attempts to conceive of CCP through a poststructuralist discursive lens, a lens that extends beyond, but certainly does not ignore, the analysis of data. In this study, we consider what we are calling poststructuralist discursive community psychology through a synthesis of poststructuralist discourse theory and CCP. Such a psychology is one that conceives of social phenomena, and indeed conceives of itself, through a poststructuralist understanding of discourse. We offer two pathways through which to consider poststructuralist discursive community psychology: re‐envisioning community and discursive consciousness‐raising. We conclude by considering some of the theoretical limitations of our discussion, as well as the areas that future work into poststructuralist discursive community psychology may enter into.